ANALISIS USAHA PEMBENIHAN GURAMI DI KECAMATAN CIBEUREUM KOTA TASIKMALAYA - , MOCHAMMAD KEVIN JULIANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Purpose of this research is to analyst and knowing cost, revenue, and R/C ratio of gouramy hatchery business. This research held at Tasikmalaya City, District Cibeureum at January until February 2014. Method to select the place for research is purposive, because the district has a huge potential of gouramy hatchery and was a center of government strategist. Research method using descriptive with survey. Descriptive is to describe about condition, profile and make a clearly difference between segment of business, then could give a recommendation after described. Data taken by survey method, using question and cost essay. To decide amount of respondent, using stratified random sampling. After stratified, to choose respondent using simple random sampling. Total amount of respondent is 40 with specification 5 for egg segment, 6 for nail segment with gouramy breeding owned, 9 for nail segment without gouramy owned, and 20 for blade segment. After analyzed, R/C ratio for egg segment is 2,64, nail without gouramy owned segment is 2,39, nail with gouramy owned is 2,42 and blade segment is 1,94. Cost for egg segment is Rp 514.715, nail with gouramy owned is Rp 3.294.847, nail without gouramy owned is 2.323.514 and blade is Rp 3.226.863. Revenue of egg segment is 1.357.000, nail segment is Rp 7.989.625, nail segment without gouramy owned is Rp 5.561.772 and blade segment is Rp 6.342.000. Recommendation for business man who has join gouramy hatchery business is to develop technology of hatchery and increase efficiency of area and feeding sector, to increase added value. Recommendation for candidate of businessman who will join gouramy hatchery business is to select nail segment without owning gouramy breeder. Because has a low risk and high return.